Synthesis and Optical Characterization of Dye Doped in Ormosil Nanospheres for Bioapplications - Duong, Vu Thi Thuy; Hoa, Do Quang; Van, Nguyen Thi; Lien, Nghiem Thi Ha; Nhung, Tran Hong; Brochon, J. C. (Communications in Physics, 2011)
Dye-doped ORMOSIL (organically modified silicate) nanoparticles (NPs) have significant advantages over single-dye labeling in signal amplification, photostability and surface modification for various biological applications. The dyes: Rhodamine 6G (R6G) and Rhodamine B (RB) were successfully incorporated into ORMOSIL nanoparticles fabricated by micellar nanochemistry from Trimethoxysilane CH_3Si(OCH_3)_3 precursor. The optical characterization of dye-doped ORMOSIL NPs was studied in comparison with it’s of free dye in solution. The results shown that the photostability of ORMOSIL dye doped nanospheres is much improved in comparison with it’s of dye in solution. Other studies of the photophysical properties such as anisotropy, fluorescence lifetime and energy transfer were also done.